Становлення суспільства знань та особливості модернізації європейської системи вищої освіти - Ярмак, Інна (Studies in Comparative Education, 2014)
Статтю присвячено висвітленню проблеми становлення суспільства знань та особливостям модернізації європейської системи вищої освіти. В статті розглянуто концепції та характеристики суспільств, які передували становленню суспільства знань, обґрунтовано необхідність суспільних змін, визначено характерні риси суспільства знань та передумови його виникнення. Схарактеризовано роль та завдання освіти в суспільстві знань. Викладено концепції провідних науковців стосовно досліджуваної проблеми та окреслено пріоритетні напрямки розвитку суспільства знань. Статья посвящена освещению проблемы становления общества знаний и особенностям модернизации европейской системы высшего образования. В статье рассмотрены концепции и характеристики обществ, предшествовавших становлению общества знаний, обоснована необходимость общественных изменений, предоставлено характерные черты общества знаний и предпосылки его возникновения. Охарактеризованы роль и задачи образования в обществе знаний. Изложены концепции ведущих ученых относительно исследуемой проблемы и намечены приоритетные направления развития общества знаний. The article is devoted to the problem of knowledge society formation and the peculiarities of modernization of European higher education system. The concepts and characteristics of societies that preceded the establishment of knowledge society are considered. The concept of industrial society is characterized by the transition from the old backward «traditional society» to the advanced, industrialized society. The industrial system is determined by high level technologies; the need for large capital investments; complexity and rise of time spent to perform industrial tasks. Due to increasing role of scientific research, the requirements for workers and managers training have risen. So there is a conflict in production sphere between present level of education and educational demands. Also the post-industrial society is highlighted. The main traces are given: economy transition from goods manufacturing to production of services; prevalence of professionals and technicians among employed workers; decision-making is made by new «intellectual technology» where the leading role is played by theoretical knowledge. In such type of society organization, processing of information and knowledge are particularly important. The ground of these processes is computer as the basis of technical revolution. The emphasis is made on technological progress that naturally leads to the emergence of the theory, where education factor is emphasized as essential part of modern society. This concept becomes a qualitatively new information society in which the economy depends on the creation, preservation and accessibility of information on national and global levels. Technology and progress influence greatly all aspects of social life, especially the sphere of education. Only qualified specialists should work on automated manufacturing. Therefore, the prestige of education is rising and the amount of middle class is increasing. The concept «information society» is defined by technology achievements and is not oriented to the person. Therefore, there is a need to transit to a qualitatively new type of society where the interaction between scientific knowledge and technology is the basis of competitiveness and people are able to generate new knowledge. Knowledge society, where information technology production is increase, as the main source of progress and economic prosperity, is determined by the author. It should be focused on the person who has information and is able to create and implement knowledge. Thus, the role of education, science and culture is increasing, providing continuous knowledge update process. Knowledge society is the society where all spheres, primarily the economy and education are focused on the latest achievements in the field of information and communication technologies. The necessity of social changes is given. The characteristics of knowledge society and the conditions of its occurrence are presented. Author determined role and purpose of life-long learning in knowledge society. The conceptions of leading scientists concerning the researched problem and main priorities on the way to knowledge society are outlined.